2018
DOI: 10.1016/j.ejvssr.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Immunofluorescent Analysis of a Large Tributary of the Great Saphenous Vein Treated with a 1920 nm Endovenous Laser: Preliminary Findings

Abstract: ObjectivesTo analyse the biological effects of a 1920 nm endovenous laser (EVL) on extra-fascial great saphenous vein (GSV) in vitro.MethodsA 10 cm length of a large tributary bypassing a hypoplastic segment of the GSV (sometimes called an “extra-fascial GSV”) was obtained during routine varicose vein surgery. The length was treated in five sections with different LEEDs (0 (control), 20, 40, 60, and 80 J/cm) with a 1920 nm EVL at 4W power, in a novel in vitro treatment model. The biological effects were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…It was previously believed that protein contraction was responsible for the efficacy of ETA. 9 Research from our own unit, using immunofluorescent analysis on an in-vitro model of transplanted extra-facial Great Saphenous Vein (GSV) treated with a 1920 nm endovenous laser disputes this, 10 as does the conclusion of another paper in the series that used a 1470 nm endovenous laser. 11 We showed that when using a Linear Endovenous Energy Density (LEED) value of 60 J/cm or above, cell death by apoptosis and necrosis occurs deep into the media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously believed that protein contraction was responsible for the efficacy of ETA. 9 Research from our own unit, using immunofluorescent analysis on an in-vitro model of transplanted extra-facial Great Saphenous Vein (GSV) treated with a 1920 nm endovenous laser disputes this, 10 as does the conclusion of another paper in the series that used a 1470 nm endovenous laser. 11 We showed that when using a Linear Endovenous Energy Density (LEED) value of 60 J/cm or above, cell death by apoptosis and necrosis occurs deep into the media.…”
Section: Introductionmentioning
confidence: 99%
“…11 We showed that when using a Linear Endovenous Energy Density (LEED) value of 60 J/cm or above, cell death by apoptosis and necrosis occurs deep into the media. 10 , 11 However, when considering endovenous laser, the optimal LEED might be different with different wavelengths and different fibre tips that vary the emitted energy distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The last issue of EJVES Short Reports (2018; 39: 7–11) included the report “Histological and immunofluorescent analysis of the large tributary of the great saphenous vein treated with a 1,920 nm endovenous laser: preliminary findings” by Ashpitel et al 1 . We have read it with great interest.…”
mentioning
confidence: 99%
“…I would like to thank Justyna Wilczko and her colleagues for their interest and comments on our work 1, 2…”
mentioning
confidence: 99%
“…With regard to the comment about vein diameter, this is of only secondary importance to the thickness of the vein wall. Ever since I proposed the idea that successful ablation needed transmural vein wall cell death in 2004, 3 and suggested that leaving a “living vein wall skeleton” of media and adventitia would allow recanalisation, 4 we have been looking at how the processes of thermal ablation and chemical ablation affect the vein wall 2, 5…”
mentioning
confidence: 99%